Mutagenic strategies against luxS gene affect the early stage of biofilm formation of Campylobacter jejuni - Teren, Martin; Shagieva, Ekaterina; Vondrakova, Lucie; Viktorova, Jitka; Svarcova, Viviana; Demnerova, Katerina; Michova, Hana T (Journal of applied genetics, 2022)
Currently, it is clear that the luxS gene has an impact on the process of biofilm formation in Campylobacter jejuni. However, even within the species, naturally occurring strains of Campylobacter lacking the luxS gene exist, which can form biofilms. In order to better understand the genetic determinants and the role of quorum sensing through the LuxS/AI-2 pathway in biofilm formation, a set of mutant/complemented strains of C. jejuni 81-176 were prepared. Additionally, the impact of the mutagenic strategy used against the luxS gene was investigated. Biofilm formation was affected by both the presence and absence of the luxS gene, and by the mutagenic strategy used. Analysis by CLSM showed that all mutant strains formed significantly less biofilm mass when compared to the wild-type. Interestingly, the deletion mutant (∆luxS) showed a larger decrease in biofilm mass than the substitution (∙luxS) and insertional inactivated ([Formula: see text]luxS) mutants, even though all the mutant strains lost the ability to produce autoinducer-2 molecules. Moreover, the biofilm of the ∆luxS mutant lacked the characteristic microcolonies observed in all other strains. The complementation of all mutant strains resulted in restored ability to produce AI-2, to form a complex biofilm, and to develop microcolonies at the level of the wild-type.
Keywords: Quorum Sensing; Biofilm formation; Bacterial Proteins; quorum sensing; Carbon-Sulfur Lyases; mutageny; Mutagens; Campylobacter jejuni; biofilmy; AI-2; lyasy štěpící vazby C-S; Signal molecules; Mutagenesis; Quorum sensing; bakteriální proteiny; Biofilms